E-Government Development in Africa: the Case of the Seychelles, Mauritius, South Africa and Botswana- Lessons for Zimbabwe - Naome Rajah; Mogopodi Lekorwe (2023)
This paper discusses the state of e-Government development in the Seychelles, Mauritius, South Africa and Botswana, allowing lessons to be drawn for Zimbabwe on how to manage its e-Government strategy. E-Government refers to the use of Information and Communications Technology (ICTs) to promote more efficient and effective government, facilitating the accessibility of government services and thus allows greater public access to information. E-Government makes governments more accountable to its citizens. A purposive sample was taken based on four countries; Seychelles, Mauritius, South Africa and Botswana, the main criterion being that the countries are in the top ten ranked countries in Africa in terms of e-Government development. Further, South Africa and Botswana are closer to Zimbabwe and also similar in demographics and therefore within reach to provide comparable and contrasting e- Government development models that may be used to inform Zimbabwe. Comparisons and contrasts of the e-Government development models of the four countries provided compelling arguments to be considered to improve on e-Government development in Zimbabwe. Desk research formed the main research methodological approach. The outcomes of the investigation are the lessons learnt from these countries and as such Zimbabwe may adopt similar strategies in order to effectively develop and implement its e-Government strategy. The following lessons were drawn: i) it was prudent for Zimbabwe to create a single point of entry for all its government e-services; ii) it was also prudent to invest in an integrated telecommunications infrastructure and human capital; iii) there was a need to fully liberalise the telecommunications sector, ICT regulatory, institutional and legal framework; and iv) there was a need to create multi- channels for online government services, converging wireless technologies as an alternative means for accessing e- Government services. Most important of all, there was an urgent need for strict implementation of e-Government projects rather than just maintaining blueprints on e- Government Development as was the case in Zimbabwe